2013
DOI: 10.1128/aem.00463-13
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptional Responses of Saccharomyces cerevisiae to d -Limonene Show Changes to the Cell Wall but Not to the Plasma Membrane

Abstract: bMonoterpenes can, upon hydrogenation, be used as light-fraction components of sustainable aviation fuels. Fermentative production of monoterpenes in engineered microorganisms, such as Saccharomyces cerevisiae, has gained attention as a potential route to deliver these next-generation fuels from renewable biomass. However, end product toxicity presents a formidable problem for microbial synthesis. Due to their hydrophobicity, monoterpene inhibition has long been attributed to membrane interference, but the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 68 publications
4
52
0
Order By: Relevance
“…Phase toxicity occurs beyond a solvent's solubility and is defined as inhibition due to a distinct second phase (2). The molecular mechanisms of phase toxicity remain poorly understood, but we have demonstrated that limonene interferes with cell wall integrity (CWI) rather than membranes in S. cerevisiae (10). Accordingly, rational strategies for alleviating toxicity, such as manipulation of membrane fluidity or expression of membranebound solvent pumps, have failed to resolve the problem of phase toxicity (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Phase toxicity occurs beyond a solvent's solubility and is defined as inhibition due to a distinct second phase (2). The molecular mechanisms of phase toxicity remain poorly understood, but we have demonstrated that limonene interferes with cell wall integrity (CWI) rather than membranes in S. cerevisiae (10). Accordingly, rational strategies for alleviating toxicity, such as manipulation of membrane fluidity or expression of membranebound solvent pumps, have failed to resolve the problem of phase toxicity (11).…”
mentioning
confidence: 99%
“…Molecular toxicity is caused by water-soluble compounds partitioning into the plasma membrane (PM) and interfering with membrane properties (9). Molecular toxicity is proportional to a solvent's aqueous concentration and reaches its maximum at a solvent's solubility point (i.e., at membrane and water saturation) (10). Phase toxicity occurs beyond a solvent's solubility and is defined as inhibition due to a distinct second phase (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A fatty acid methyl ester (FAME) analysis was performed on the extracted lipids from section 3.3.6 as previously described (Brennan et al, 2013). The lipid solid was dissolved in hexane and 5.1 μg of nondecanoic acid (Sigma-Aldrich, St. Louis, MO, USA) was used as an internal standard (ISTD) to a final concentration of 3.6 μg / mL.…”
Section: Fatty Acids and Sterolsmentioning
confidence: 99%
“…The lipid solid was dissolved in hexane and 5.1 μg of nondecanoic acid (Sigma-Aldrich, St. Louis, MO, USA) was used as an internal standard (ISTD) to a final concentration of 3.6 μg / mL. Saponification, methylation and GC/MS analysis of the lipid mass fraction followed the protocol described in (Brennan et al, 2013). The software program AMDIS (version 2.64, National Institute of Standards and Technology (NIST), Gaithersburg, MD, USA) was used for the analysis of the fatty acid and sterols.…”
Section: Fatty Acids and Sterolsmentioning
confidence: 99%